Identification of a novel TP63 mutation causing nonsyndromic cleft lip with or without cleft palate - Tianhui Xu; Mengmeng Du; Xinhua Bu; Donglan Yuan; Zhiping Gu; Pei Yu; Xuefang Li; Jiao Chen; Chunyan Jin (BMC, 2021)
Abstract Background Cleft lip with or without cleft palate (CL/P) is the most common craniofacial anomaly with a high incidence of live births. The specific pathogenesis of CL/P is still unclear, although plenty of studies have been conducted. Variations of tumor protein 63 (TP63) was reported to be related to the phenotype of CL/P. The case discussed in this report involves a pedigree with mutation at TP63 gene, and the variation was not reported before. Case presentation A Chinese pedigree with CL/P was collected in this study. The proband is a 3-year-old boy with the phenotype of CL/P, while his global development and intelligence are normal. After two CL/P repair operations, he looks almost normal. The proband's uncle and grandmother both have the phenotype of CL/P. Cytogenetic analysis and chromosomal microarray analysis (CMA) were performed, followed by whole exome sequencing (WES) and sanger validation. Analysis of WES revealed a variant of C>T at nucleotide position 1324 (1324C>T) of TP63 gene, possibly producing a truncated protein with a premature stop codon at amino acid position 442 (p.Q442*). This mutation was localized at the oligomerization domain (OD) of TP63 and might impair the capacity of p63 oligomerization. Conclusion The mutation in TP63 was recognized to be the possible cause of the phenotype of CL/P in this pedigree. This report provides some evidence for the clinical diagnosis of CL/P. And our study also provides clinical evidence for the molecular mechanism of TP63 gene causing nonsyndromic cleft lip with or without cleft palate (NSCL/P).